STUDY OF THE EFFECT OF WHEAT GERM EXRACT ON THE PRODUCTION OF EXOPOLYSACCHARIDES FROM THE BIO-ENHANCERS - & Apd- Aljabar, Al- Mousawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The objective of this study was to investigate effect of wheat germ extraction on the fermented milk products, which prepared using single and two types of mixed cultures of Lactobacillus acidophilus, Lactobacillus plantarum, ready premixed and 1: 1 mixture with inoculation of 5% in reconstituted skimmed milk 12% TS Which reinforced with different concentrations of wheat germ extracts 0, 5, 10 and 15% for treatments (T1, T2, T3 and T4) respectively. The results showed that the height of the viscosity of all the products increased by the percentage of added wheat germ extract. The best treatment (10%) of T3, which was 52, 65, 57 and 64 mpa for each of the types of bacterial starter culture in the above respectively, compared to the reduction in the ratio of T4 (15%) was 51 and 63, 55 and 60 mpa. Furthermore The treatment of 10% (T3) showed the best production of exopolysaccharides (4.518, 4.869, 4.524, 4.668 mg / ml) and reduction with T4 (15%) to 3.870, 4.784, 4.275 and 4.049 mg . for each of the above probiotics cultures used in processing of fermented dairy products, The results showed that Lb. Plantarum is the most efficient in the production of exopolysaccharides, compared to other starter cultures bacteria and its role in increasing the viscosity and improve the strength of the probiotics fermented milk product treatment is a good qualities according to the Iraqi standard (milk fermented therapeutic).